2003
DOI: 10.1890/0012-9658(2003)084[1800:pvolaa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation of Larks Along an Aridity Gradient: Are Desert Birds More Flexible?

Abstract: We investigated interindividual variation and intra‐individual phenotypic flexibility in basal metabolic rate (BMR), total evaporative water loss (TEWL), body temperature (Tb), the minimum dry heat transfer coefficient (h), and organ and muscle size of five species of larks geographically distributed along an aridity gradient. We exposed all species to constant environments of 15°C or 35°C, and examined to what extent interspecific differences in physiology can be attributed to acclimation. We tested the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
135
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 41 publications
(40 reference statements)
5
135
1
Order By: Relevance
“…This is in line with adjustments of basal MR in birds to hot environments. Differences in basal MR between populations from different regions could be explained by genetically based differences in the response to the same environmental gradient (Tieleman et al 2003). Thus, basal MR appears to be a plastic character, because foster birds from the southern population strongly react to changes in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with adjustments of basal MR in birds to hot environments. Differences in basal MR between populations from different regions could be explained by genetically based differences in the response to the same environmental gradient (Tieleman et al 2003). Thus, basal MR appears to be a plastic character, because foster birds from the southern population strongly react to changes in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies within species have shown correlations between BMR and masses of central organs (Brzek et al, 2007;Chappell et al, 1999;Even et al, 2001;Piersma et al, 1996), but other studies have failed to find correlations between BMR and sizes of central organs within species (Geluso and Hayes, 1999;Russell and Chappell, 2007). In some interspecific comparisons, authors have elucidated positive correlations between BMR and sizes of some organs (Daan et al, 1990;Raichlen et al, 2010), but other studies have failed to find such an association (Tieleman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Serventy 1971;Fisher et al 1972;Davies 1976;Main 1976;Schodde 1982;Withers and Williams 1990;Schleucher 1993;Tieleman et al 2003;Byrne et al 2008;Robin et al 2009). Predictions concerning regional biogeographic patterning, however, have not been tested thoroughly.…”
Section: Introductionmentioning
confidence: 99%